Representation of Feminity in the 16th Century: The Main Character in Kei Ookubo's Anime Arte Series - Marselana, Sela; Seruni, Ayu Putri (Chi e Journal of Japanese Learning and Teaching, 2024)
Women in the renaissance era were portrayed as weak, emotional and illogical. This made it obligatory for women to be in the domestic sector, namely taking care of household affairs and limiting women to work. Until finally feminism was born in women who craved freedom. Today, feminism is present in various forms of literary works, one of which is the anime series Arte by Kei Ookubo. The purpose of this study is to analyze the basic character of feminism in the main character of the anime series Arte, Analyzing the internal and external factors of the emergence of the spirit of feminism. Both objectives are analyzed based on Sarah Gwyneth Ross's theory of feminism.This research uses a qualitative analysis description method with a literary feminism approach. This research uses a literature study where the object of research is the anime Arte which is researched using Sarah Gwyneth Ross's theory of feminism. It was found that Arte fulfills the five basic characters of feminism. First, Arte maintains she excellence in the arts. Second, Arte has intelligence equal to men. Third, the masculinity shown by Arte is the courage to speak up. Fourth, Arte understands the discrimination experienced by women so that she appreciates and praises women's hard work. Fifth, Arte has high creativity. Arte's inner voice to highlight she artistic talent is an internal factor in the formation of feminism. Meanwhile, the figure of father is an external factor in the formation of feminism.